European economic policy and the European Green Deal: An institutionalist analysis - Sibylle Treude (Hochschule Koblenz - University of Applied Sciences, Fachbereich Wirtschaftswissenschaften, 2022)
The article deals with the influence of the European Commission in the field of economic policy in the European Union (EU) since the beginning of the 21st century. Starting from reflections on the guiding idea of supranationality the question arises if and how the Commission has increased its influence on the economic policies of the EU Member States. The role of the EU's long-term strategies like the European Green Deal are analysed by applying the approach of Evolutionary Institutionalism. Has the European Commission induced institutional change and improved its own institutional fitness? Which role does the European Green Deal play in European economic policy?
Keywords: 650; European integration; EU; European economic policy; European Green Deal; European integration theory/approaches; Evolutionary Institutionalism